SARS-CoV-2 Seroprevalence in Florida Department of Health in Palm Beach County Obstetric Clinics: A Cross-Sectional Study during the First Pandemic Surge - Gonik, Charles O.; Alonso, Alina M.; Gonik, Bernard (American Journal of Perinatology, 2021)
Objective Estimating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seroprevalence is an important part of the public health approach to coronavirus disease 2019 (COVID-19) understanding and containment. This is particularly relevant to an obstetric population because of implications in the management of the pregnant host, care of the newborn, and disease progression within the community.Study Design A cross-sectional seroprevalence study was performed in four Department of Health Palm Beach County clinics from June 29, 2020, to August 5, 2020. Samples were collected from asymptomatic antepartum and postpartum participants. A web-based surveillance system was used to identify subsequent antibody or polymerase chain reaction (PCR) testing encounters.Results A total of 163 of 618 subjects were seropositive (26.4%). Racial makeup was white 2.5%, black 19.0%, and Hispanic 78.5%. Positive serology was seen in 16.0, 35.6, and 30.1% of first, second, and third trimesters, respectively; 18.4% were positive postpartum. Only four patients voluntarily reported PCR positivity prior to antibody testing. Six home zip codes accounted for the majority (68.1%) of positive results. Thirty-two patients had repeat serology (65.6% positive and 34.4% negative). Of the 163 subjects, 65 underwent later PCR testing with 92% negative for SAR-CoV-2.Conclusion Almost one in four subjects had serologic evidence of previous SARS-CoV-2 infection. These very high seroprevalence rates have not been previously reported and highlight the concern for health disparities in the United States. Most were asymptomatic and without a history for SARS-CoV-2 exposure. There was a loss of seropositivity in a significant number of subjects, raising concern for risk of reinfection, inadequate transplacental antibody transfer, and subsequent limited passive protection to the newborn. These seroprevalence data will also allow for better newborn follow-up of unanticipated consequences of COVID-19 infection in pregnancy.Key Points
Keywords: SARS-CoV-2; epidemiology; pregnancy; seroprevalence